CAMPUS SUSTAINABILITY: MEASURING AWARENESS OF SUSTAINABLE DEVELOPMENT DIMENSIONS AMONG EDUCATORS IN MALAYSIAN UNIVERSITY - Sharmila Rani Moganadas; Subhacini Subramaniam; Nun Shwu Huey; Ainee Suriani Bahaman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Sustainable development has long gained momentum as an indispensable change-maker of the present and future, across nations, organisations, institutions, and individuals around the globe. Despite its universal recognition, the understanding of the concept’s constituents seems vague and heterogeneous, which has led to piecemeal initiatives that appear to impede the vision of systemic sustainability. In this disposition, many experts reckon that the higher education institutions that are in the sustainably adept nick, capable of cultivating and leading the community towards a holistic sustainable development approach. This portrays the need for a sound knowledge or awareness of sustainable development dimensions among campus actors; in particular, the educators, as it emerges as the prerequisite to campus sustainability endeavours. This paper, therefore, aims to carry out one of the grassroots level efforts, which is to measure the awareness of sustainable development dimensions among academic staff of a private university in Malaysia. This research adopted an online and offline survey to obtain responses from 169 educators. The findings show that there are significant differences in the level of awareness on sustainable development dimensions (economy, social, and environment) among educators of the university. Gaps and needs identified in this study can be useful to the management to better orientate their actions towards campus sustainability plans, such as policies, curriculum development, operations, research, etc.